Mapping the Landscape of Cyber Law and Fingerprints: A Data Analysis of Scholarly Works - Bagus Afianto; Emy Rosnawati; Suyo Gigih Prasetyo (Proceedings of The ICECRS, 2023)
This data article presents a comprehensive analysis of scholarly works on the intersection of Cyber Law and fingerprints. Using the lens.org database, we employed specific filters, including the document type (Journal article) and subject (Law), to retrieve relevant articles. We examined nine key visualizations to explore the fields of study covered by active institutions, identify prolific authors, highlight leading countries in this domain, track scholarly works over time, visualize relationships within scholarly works, pinpoint top fields of study, unveil prominent institution names, reveal top journals by publishers, and spotlight influential publishers. These insights provide a valuable overview of the trends and key players in the Cyber Law and fingerprints domain, aiding researchers and policymakers in understanding the current state of this field and its implications.Highlights : Comprehensive analysis of Cyber Law and fingerprints scholarly works. Reveals key trends, authors, and institutions in this domain. Provides valuable insights for researchers and policymakers. Keywords: Cyber Law, Fingerprints, Data Analysis, Scholarly Works, Trends